The Effectiveness of Breathing Exercises on the Physiological and Psychological Variables of Patients with Pulmonary Tuberculosis - Shakuntala; Jaspreet Kaur; Monisha.K.Masih; Jyoti Sarin (Indian Journal of Forensic Medicine & Toxicology, 2021)
A study to evaluate the effectiveness of breathing exercises on physiological and psychological variables of patientswith pulmonary tuberculosis in selected hospital at Ambala, Haryana.TB is a 7th killer disease in the world and one of the top 10 causes of death. Pulmonary tuberculosis (PTB) is aninfection, which causes widespread pulmonary fibrosis and cavitation, and often leaves the patient with a chronicrespiratory deficit as a result.Aims and Objectives: The aim of the study was to evaluate the effectiveness of breathing exercises on physiologicaland psychological variables of patients with pulmonary tuberculosis.Material and Methods: A quasi experimental design using non-equivalent control group pretest- posttest designwas conducted on 110 pulmonary tuberculosis patients (55 in comparison group and 55 in experimental group) inDOTS center of UPHC RavidasMajriInderpuri colonyAmbala city, UPHC Baldev NagarAmbala city, UPHC DurgaNagar Ambala city and CHC Mullana. The dependent variables were physiological variables (dyspnea, spo2, heartrate, respiratory rate) and psychological variables (anxiety, quality of life). Pretest was taken in UPHC Durga NagarAmbala city and CHC Mullana on day 1 and posttest was taken inUPHC RavidasMajriInderpuri colonyAmbala cityand UPHC Baldev NagarAmbala cityon day 30. In experimental group, breathing exercises were administered by theresearcher two times a week. Each session was of 30 minutes including 4 breathing exercises (pursed lip breathingexercise, diaphragmatic breathing exercise, deep breathing exercise and segmental breathing exercise) and eachexercise was performed for 6-8 times. Other days patients were estimated to perform breathing exercises themselvesat home and on day 30, posttest was taken.Results: Both the groups were homogenous with respect to physiological and psychological variables before theadministration of breathing exercises. On day 30, the mean dyspnea score and anxiety score of experimental groupwas significantly lower than comparison group (p<0.05). The quality of life of patients in experimental group wassignificantly better than comparison group at day 30.Conclusion:Based on the findings of the study, it can be concluded that breathing exercises are effective in reducingthe dyspnea, anxiety, HR and RR. Breathing exercises are effective in improving theO2saturation, blood pressure andquality of life among pulmonary tuberculosis patients.